2011
DOI: 10.1111/j.1552-6569.2009.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging of Guillain-Mollaret Triangle in Patients with Hypertrophic Olivary Degeneration

Abstract: A B S T R A C TThe aim of the study is to analyze diffusion tensor imaging (DTI) characteristics of the Guillain-Mollaret triangle (GMT) in patients with hypertrophic olivary degeneration (HOD) and to investigate their correlation with previously reported histopathology. DTI was performed in 10 patients diagnosed with HOD. Fractional anisotropy, apparent diffusion coefficient, axial diffusivity, and radial diffusivity were measured in the inferior olivary nucleus (IO), the central tegmental tract, the red and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
6
26
0
Order By: Relevance
“…1 B-D; Table S2) (9,10). The MRI scans were also remarkable for obvious cerebellar and mild cerebral atrophy that was more severe in the older siblings ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 B-D; Table S2) (9,10). The MRI scans were also remarkable for obvious cerebellar and mild cerebral atrophy that was more severe in the older siblings ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All MRI examinations were performed in a 3T scanner (Trio, Siemens) using 8-channels head coil. The DTI datasets were obtained and analyzed as described before (9). Briefly, high resolution cranial MRIs were performed using the following sequences: sagittal TSE T2, axial SE T1, TSE T2, FLAIR and diffusion, coronal TSE T2, high resolution 3D TurboFlair T2 and reconstructions, sagittal 3D TurboFlash T1 and reconstructions, sagittal 3D SPACE T2 and reconstructions, coronal optic nerve focused TSE -STIR, SE T1, DTI-FT, axial GRE T2.…”
Section: Methodsmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) studies in patients with inferior olivary nucleus hypertrophy have demonstrated signal changes in all anatomical components of the Guillain-Mollaret triangle even when conventional MRI did not show any signs of involvement in the other components of the Guillain-Mollaret triangle. 39,40 It was also shown that the DTI parameters can reflect the spatiotemporal evolution of transneuronal degeneration associated with hypertrophic olivary degeneration (HOD) in a manner consistent with the known pathological stages of HOD. 26 In addition, susceptibility-weighted imaging has been utilized to study the red nucleus degeneration and atrophy in children with HOD after posterior fossa tumour resection.…”
Section: Discussionmentioning
confidence: 99%
“…5,13,15 Recent cross-sectional studies in children and adults with HOD showed that DTI can demonstrate and quantify the disruption of the GMT's components. 4,12,17 However, HOD is a dynamic process, and progressive changes have been shown by neuropathological examination and conventional MRI.…”
Section: Diffusion Tensor Imaging (Dti) Is An Advanced Mrimentioning
confidence: 99%
“…5,13,15 Recent cross-sectional studies in children and adults with HOD showed that DTI can demonstrate and quantify the disruption of the GMT's components. 4,12,17 However, HOD is a dynamic process, and progressive changes have been shown by neuropathological examination and conventional MRI.6,7 The purpose of this study is to investigate longitudinal DTI changes of the GMT's components in a child with HOD after neurosurgery for a midbrain tumor.Hypertrophic olivary degeneration in a child following midbrain tumor resection: longitudinal diffusion tensor imaging studies Hypertrophic olivary degeneration (HOD) is a dynamic process caused by disruptive lesions affecting components of the Guillain-Mollaret triangle (GMT). The authors applied diffusion tensor imaging (DTI) to investigate longitudinal changes of the GMT components in a child with HOD after neurosurgery for a midbrain tumor.…”
mentioning
confidence: 99%